Some helminth parasites of marine fishes of south Africa: family Opecoelidae (Digenea) - Bray, R. A. (Journal of Natural History, 1987)
The following digeneans are described, recorded or figured from South African waters: Pseudopecoelus ablennesi sp. nov. from Ablennes hians; Coitocaecum capensis sp. nov. from Clinus superciliosus, C. cottoides, Gynutoclinus rotundifrons, Xenopoclinus kochi and X. leprosus; Dactylostomun griffithsi sp. nov. from Cheilodactylus fasciatus; Margolisia vidalensis gen. nov., sp. nov. from Trachinocephalus myops; Pachycreadium obovatum from Sparodon durbanensis, Diplodus cervinus and Cheilodactylus fasciatus; Allopodocotyle recifensis sp. nov. from Pterogymnus laniar; Helicometra fasciata in Arius feliceps, Chirodactylus brachydactylus, Clinus capensis, C. cottoides, C. superciliosus, Gynutoclinus rotundifrons, Pachymetopon blochii, Pomadasys olivaceus, Pomatomus saltator, Xenopoclinus kochi and X. leprosus; Helicometrina nimia from Rhonciscus anus. The other taxa discussed are the genera Pseudopecoelus, Coitocaecum (synonyms Ozakia, Pseudocoitocaecum, Paradactylostomum), Dactylostomum, Pachycreadium and Allopodocotyle. In discussion the following new combinations are made: Coitocaecum (formerly Pseudocoitocaecum) bombayensis (Ahmad, 1983); C. (formerly P.) thrissoclesis (Bilqees, 1972); Dactylostomum (formerly Ozakia) iniistii (Yamaguti, 1970); D. (formerly O.) pfluegeri (Yamaguti, 1970); D. (formerly Coitocaecum) xesuri (Yamaguti, 1940); Allopodocotyle (formerly Podocotyle (Pedunculotrema) israelense (Fischthal, 1980); Allopodocotyle (formerly Podocotyle) jaffensis (Fischthal, 1980).